Plasma bactericidal activity after administration of erythromycin estolate and erythromycin ethylsuccinate to healthy volunteers. - Bérubé, D (1988)
In a crossover design study, we compared the plasma bactericidal activities of erythromycin estolate (500 mg) and erythromycin ethylsuccinate (600 mg) after administration of a single oral dose to 12 healthy volunteers. Both erythromycin esters displayed very good plasma bactericidal activities against Streptococcus pneumoniae. The median bactericidal titers produced in plasma against Streptococcus pyogenes and Streptococcus pneumoniae were significantly higher with erythromycin estolate than with the ethylsuccinate ester at both 2 and 8 h after dosing (P less than 0.05 by Student's t test). Both erythromycin esters showed rather weak bactericidal activity against Branhamella catarrhalis; a further look at these results indicated that erythromycin estolate presented 50% of the plasma samples at 2 h with bactericidal titers superior or equal to 1:8, versus 11% for the ethylsuccinate ester. Of the 60 plasma bactericidal activity tests performed against Staphylococcus aureus, only 6 (10%) and 3 (5%) exhibited titers of 1:8 or greater for erythromycin estolate and erythromycin ethylsuccinate, respectively. Clinical trials are warranted in which these products are compared in infections other than Streptococcus pyogenes pharyngitis, for which the clinical superiority of erythromycin estolate has been demonstrated.